المواطنة البيئية بين الواقع والتنظير - تومى, الخنساء (جامعة الوادي - University of Eloued, 2023)
شهدت المجتمعات المعاصرة مشكلات بيئية عديدة شكلت مخاطر على حياة الإنسان بصفة خاصة، وحياة الكائن الحي بصفة عامة، وهذا نتيجة تدخل الإنسان وتأثيره في البيئةـ، فأساء إليها من نواحي عديدة بقصد ودون قصد، لذلك تتعالى النداءات والتنبيهات بضرورة الاهتمام بالمشكلات البيئية التي تتفاقم يوما بعد يوم. وبهذا الصدد تم سن القوانين والتشريعات البيئية للحفاظ على البيئة، ومع ذلك لا تزال هناك العديد من الممارسات التي تضر بالبيئة، ويعتبر الوعي البيئي، و توعية المواطن بمسؤوليته تجاه البيئة من أهم الطرق الضرورية والمجدية التي تجعل المواطن يحترم القوانين المنظمة للتعامل مع البيئة والمساهمة في حل مشكلاتها، وهو ما يطلق عليه بالمواطنة البيئية ونحن في هذه المداخلة نحاول توضيح هذا المفهوم، وأبعاده، والذي أصبح أداة فعالة لتحقيق التنمية المستدامة، من خلال ما يلي:ماذا نعني بالمواطنة البيئية؟ ما هي أهدافها؟ ما هي مؤشراتها؟ ما هي أهميها بالنسبة للفرد والمجتمع؟. Abstract: This article aims to define the theoretical framework of George Siemens' Connectivism Theory and to explain its importance in the learning process in the context of continuous knowledge development and contemporary learner needs. It first addressed the philosophy of Connectivism Theory as an introductory approach, then focused on its academic concept, followed by its procedural implications according to educational practices, to be a digital ground on which learning in electronic environments is influenced by social dynamics and reinforced by technology. Drawing on different theoretical references and national regulations, the article concluded with a case study of Tunisia in employing Connectivism Theory procedures in higher education during the Covid-19 pandemic (the Tunisian Virtual University as a model) and highlighted the role of Connectivism Theory in achieving pedagogical renewal and educational quality in the educational system through electronic interactive network processes among learners, based on learning processes and changing teacher roles.
مقال
Keywords: النظرية الاتصالية,التعليم,المعلم,المتعلم,البيئات الرقمية; Connectivism Theory, Education, Digital Environments, Teacher, Learner